Energy Technology 2015 Carbon Dioxide Management and Other Technologies - Jha, Animesh; Wang, Cong; Neelameggham, Neale; Guillen, Donna; Li, Li; Belt, Cynthia; Kirchain, Randolph; Spangenberger, Jeffrey; Johnson, Frank; Gomes, Andrew; Pandey, Amit; Hosemann, Peter (The Minerals, Metals & Materials Series, 2016)
This book covers various technological aspects of sustainable energy ecosystems and processes that improve energy efficiency, and reduce and sequestrate carbon dioxide (CO2) and other greenhouse emissions. Papers emphasize the need for sustainable technologies in extractive metallurgy, materials processing and manufacturing industries with reduced energy consumption and CO2 emission. Industrial energy efficient technologies include innovative ore beneficiation, smelting technologies, recycling, and waste heat recovery. The book also contains contributions from all areas of non-nuclear and non-traditional energy sources, including renewable energy sources such as solar, wind, and biomass. Papers from the following symposia are presented in the book: Energy Technologies and Carbon Dioxide Management Recycling and Sustainability Update Magnetic Materials for Energy Applications V Sustainable Energy and Layered Double Hydroxides.